Pengaruh Model Pembelajaran SAVI (Somatis, Auditori, Visual, dan Intelektual) Terhadap Kemampuan Literasi Numerasi dan Self-Efficacy Matematika Siswa di Sekolah Menengah Atas - Alfi Fatmawati; Nuryadi (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model on the mathematical self-efficacy and numeracy literacy of grade XII students at SMA Negeri 1 Sedayu. The study used a quasi-experimental method with a non-equivalent control group design. The research sample consisted of an experimental group that received SAVI learning and a control group that used conventional learning. Data were collected through a validated mathematical self-efficacy questionnaire and a numeracy literacy test. Data analysis was carried out using the Independent Sample t-test and the N-Gain test with the help of SPSS 25. The results showed a significance value of 0.020 for the self-efficacy variable and 0.005 for the numeracy literacy variable, which means there is a significant effect of the SAVI model compared to conventional learning. In addition, the results of the N-Gain test showed a moderate increase, namely 0.37 for self-efficacy and 0.52 for numeracy literacy. These findings indicate that the SAVI learning model is effective in improving students' mathematical self-efficacy and numeracy literacy through active, multisensory, and collaborative learning engagement.